Mineral composition and assessment of human ingestion risk of twelve accessions of Moringa oleifera Lam - Ansah, M Owusu; Asare, D K; Amoatey, H M; Gyamfi, E T; Bentil, N O (Journal of Ecobiotechnology, 2012)
Increasing consumption of moringa leaf powder in Ghana is boosted by popular claims that the plant contains a rich array of minerals, vitamins and other protective substances. However, the safe doses of this product among gender classes and vulnerable groups are unknown. This knowledge gap demands an analysis of the mineral composition of the product and estimation of the risk (hazard) potential associated with the ingestion of dried leaf samples of the moringa plant. Mineral composition (Na, Mg, P, K, Ca, Mn, Cr, Fe, Cu and Zn) of dried leaf samples of twelve accessions of Moringa oleifera Lam. was determined using the Atomic Absorption Spectrometry aided by a fast sequential Atomic Absorption Spectrometer. Results of the study indicate that the samples showed variation with respect to macro and micro minerals content and that dried leaf powder of moringa can serve as an excellent source of minerals. Additionally, an estimation of hazard exposure calculated as hazard index presented overall indices of 0.0866 and 0.0443 for males and females respectively. Even though the values (0.076-0.097; 0.038-0.051) obtained from the samples are within safe limits, it is essential that consumption of moringa leaf powder is done on sound advice from a nutritionist since crucial factors such as gender, age, health status and exposure time contribute to individual dose needs and influence mineral toxicity.